A business practice of sufficiency economy philosophy: a contribution to performance of new product. (2017) - Siriphanupong, Thammawich; Rungkasiri, Tippakorn
This study aims to evaluate the success of new product using a business theory of sufficiency economy in term of financial and non-financial. This study was conducted mixed methods (qualitative research and quantitative research), by in-depth interview and questionnaire, for collecting data from persons who directly involved in new product development and adopted the sufficiency economy philosophy to conduct the business. The business operation by adopting the concept of sufficiency economy philosophy was similar to sustainable development, in order to support balance among economy, society and environment and enable the organisations to build a strong foundation for sustainable business. The results shown that there were reflected positive impact on the performance of new product using a business practice of sufficiency economy philosophy.